2022
DOI: 10.3390/cancers14122842
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Analysis Points to Bioactive Lipid Species and Acireductone Dioxygenase 1 (ADI1) as Potential Therapeutic Targets in Poor Prognosis Endometrial Cancer

Abstract: Metabolomic profiling analysis has the potential to highlight new molecules and cellular pathways that may serve as potential therapeutic targets for disease treatment. In this study, we used an LC-MS/MS platform to define, for the first time, the specific metabolomic signature of uterine serous carcinoma (SC), a relatively rare and aggressive variant of endometrial cancer (EC) responsible for 40% of all endometrial cancer-related deaths. A metabolomic analysis of 31 ECs (20 endometrial endometrioid carcinomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Comparison of metabolic profiles in tissue samples to urine and brushing samples showed that 49 of 74 metabolites were also detected in urine samples and 21 of 74 metabolites in intrauterine brushing samples, which supports the potential of urine metabolomics profiles for non-invasive diagnostic/prognosis ( Supplementary Table S8 ). A recent study explored the metabolic profiles in biobanked tissue samples from endometrioid (n=20) and serous EC (n=11) ( 153 ). Using non-targeted MS analysis, 232 metabolic differences could be characterised ( Supplementary Table S8 ).…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of metabolic profiles in tissue samples to urine and brushing samples showed that 49 of 74 metabolites were also detected in urine samples and 21 of 74 metabolites in intrauterine brushing samples, which supports the potential of urine metabolomics profiles for non-invasive diagnostic/prognosis ( Supplementary Table S8 ). A recent study explored the metabolic profiles in biobanked tissue samples from endometrioid (n=20) and serous EC (n=11) ( 153 ). Using non-targeted MS analysis, 232 metabolic differences could be characterised ( Supplementary Table S8 ).…”
Section: Resultsmentioning
confidence: 99%
“…Metabolomics studies also revealed that arachidonic acid, stearic acid, and linoleic acid metabolites enrolled in lipid metabolism were lowered in advanced-stage and nonendometrioid EC samples. 60 , 61 , 62 Building upon the insights gained from multi-omics analysis, we hypothesized that focusing on subtype-specific metabolic characteristics that significantly influence tumor behavior within the MPS subtypes may provide useful targeted therapy strategies in EC, but these need further validation in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The increased concentrations of microbially derived tryptophan and propionate can cause mitigation of gastrointestinal syndromes, long-term radioprotection, and reduction in proinflammatory responses [112]. Different metabolites among the uterine serous carcinoma and endometrial cancer were discovered, and most belonged to purine nucleotides and amino acids, including 2-oxo-4-methylthiobutanoic acid synthesized via the acireductone dioxygenase 1 enzyme, which are potential therapeutic targets in poor-prognosis serous carcinoma patients [113].…”
Section: Modulating Metabolism Analysis Using Mass Spectrometrymentioning
confidence: 99%